Optimizing the Empowerment of Mumbul Tourism Park as an Alternative Effort to Restore Sangeh Tourism Village After the Covid-19 Pandemic in Badung Regency - Putu Eka Trisna Dewi; Vinsensius Jala; I Wayan Ariyarta; Anak Agung Gede Triyatna; Made Adi Kusuma; I Gde Oka Suparyana; Hendro Ponco Raharjo (Law Doctoral Community Service Journal, 2023)
The Island of Bali is famed for its nature beauty; therefore, the many tourism potentials being developed into tourist attractions must be able to attract tourists to visit Bali. Sangeh Tourism Village is one of the tourism villages in Badung Regency which is rich in various potentials. Unfortunately, since the Covid-19 pandemic until after the pandemic, tourist visits have decreased significantly. To overcome this, one of the tourist attractions having the potential to be developed in the Sangeh Tourism Village is the Mumbul Tourism Park. The advantages of the Mumbul Tourism Park are in terms of nature and spirituality so it can still be optimally developed and promoted in order to increase the tourism development of the Sangeh Traditional Village with a positive impact on Regional Original Revenue (PAD).